Pathogenesis of depression and the potential for traditional Chinese medicine treatment - Ding, Weixing; Wang, Lulu; Li, Lei; Li, Hongyan; Wu, Jianfa; Zhang, Jing; Wang, Jing (Frontiers in Pharmacology, 2024)
Depression is a prevalent mental disorder that significantly diminishes quality of life and longevity, ranking as one of the primary causes of disability globally. Contemporary research has explored the potential pathogenesis of depression from various angles, encompassing genetics, neurotransmitter systems, neurotrophic factors, the hypothalamic-pituitary-adrenal axis, inflammation, and intestinal flora, among other contributing factors. In addition, conventional chemical medications are plagued by delayed onset of action, persistent adverse effects, and restricted therapeutic efficacy. In light of these limitations, the therapeutic approach of traditional Chinese medicine (TCM) has gained increasing recognition for its superior effectiveness. Numerous pharmacological and clinical studies have substantiated TCM's capacity to mitigate depressive symptoms through diverse mechanisms.This article attempts to summarize the mechanisms involved in the pathogenesis of depression and to describe the characteristics of herbal medicines (including compounded formulas and active ingredients) for the treatment of depression. It further evaluates their effectiveness by correlating with the multifaceted pathogenesis of depression, thereby furnishing a reference for future research endeavors.